Concussion clinic presentation and symptom duration for pediatric sports-related concussions following Ohio concussion law. Issue 1 (2nd January 2019) - Cuff, Steven C.; Coxe, Kathryn; Young, Julie A.; Li, Hongmei; Yi, Honggang; Yang, Jingzhen
ABSTRACT: In 2013, Ohio enacted a law to mitigate consequences of pediatric sports-related concussions. This study aimed to describe changes in clinic visits and symptom duration for pediatric sports-related concussions before and after this law. 3, 133 new visits by 2, 861 unique patients (10–18 years) presenting between April 2012 and April 2015 for sports-related concussions within 30 days of injury were included. There were 937 (29.9%), 1, 132 (36.1%) and 1, 064 (34.0%) concussion visits for pre-law, immediate-post law, and post-law periods, respectively. A greater proportion of concussion visits was observed among females from pre-law to post-law (P < 0.0001). No differences were observed across the three periods in symptom scores at injury (P = 0.5028) or at first clinic visit (P = 0.5686). However, patients presented to concussion clinics significantly earlier (17.6 vs. 22.8 days, P < 0.0001) and had quicker recovery (26.5 vs. 40.6 days, P < 0.0001) post-law than pre-law.